Association between pneumonia in acute stroke stage and 3-year mortality in patients with acute first-ever ischemic stroke. (November 2016) - Yu, Yi-Jing; Weng, Wei-Chieh; Su, Feng-Chieh; Peng, Tsung-I; Chien, Yu-Yi; Wu, Chia-Lun; Lee, Kuang-Yung; Wei, Yi-Chia; Lin, Shun-Wen; Zhu, Jun-Xiao; Huang, Wen-Yi
Highlights: The influence of pneumonia on stroke outcome is still controversial. We investigate the influence of pneumonia on ischemic stroke outcome. Pneumonia in acute stroke stage is associated with increased risk of mortality. Preventing pneumonia in the acute stroke stage might improve stroke outcome. Abstract: The influence of pneumonia in acute stroke stage on the clinical presentation and long-term outcomes of patients with acute ischemic stroke is still controversial. We investigate the influence of pneumonia in acute stroke stage on the 3-year outcomes of patients with acute first-ever ischemic stroke. Nine-hundred and thirty-four patients with acute first-ever ischemic stroke were enrolled and had been followed for 3 years. Patients were divided into two groups according to whether pneumonia occurred during acute stroke stage or not. Clinical presentations, risk factors for stroke, laboratory data, co-morbidities, and outcomes were recorded. The result showed that a total of 100 patients (10.7%) had pneumonia in acute stroke stage. The prevalence of older age, atrial fibrillation was significantly higher in patients with pneumonia in acute stroke stage. Total anterior circulation syndrome and posterior circulation syndrome occurred more frequently among patients with pneumonia in acute stroke stage ( P < 0.001 and P = 0.009, respectively). Multivariate Cox regression revealed that pneumonia in acute stroke stage is a significant predictor of 3-year mortality (hazard ratio = 6.39, 95% confidence interval = 4.03–10.11, P < 0.001). In conclusion, pneumonia during the acute stroke stage is associated with increased risk of 3-year mortality. Interventions to prevent pneumonia in acute stroke stage might improve ischemic stroke outcome.